2020
DOI: 10.1177/1368430220960795
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact fosters more inclusive social identities

Abstract: We examined how people construct their social identities from multiple group memberships—and whether intergroup contact can reduce prejudice by fostering more inclusive social identities. South Indian participants ( N = 351) from diverse caste backgrounds viewed 24 identity cards, each representing a person with whom participants shared none, one, two, or all of three group memberships (caste, religion, nationality). Participants judged each person as “us” or “not us,” showing whom they included in their ingro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Identifying that such a phenomenon produces the assimilation of characteristics, desires, and the establishment of bonds, generating emotional and evaluative significance of subsidized membership within a social system, instrumentalizes actions aimed at health promotion. The evidence recovered in this study indicates the need for collective actions to promote or maintain the social support for members of the trans community (21,(25)(26)(27) ; the role of the media (28) ; the support of friends, family, and other contacts of significance to the person (27) ; and greater family involvement in the transition process (27) , since these are factors that precede the formation of a social identity for the transgender person.…”
Section: Defining Characteristicsmentioning
confidence: 78%
See 2 more Smart Citations
“…Identifying that such a phenomenon produces the assimilation of characteristics, desires, and the establishment of bonds, generating emotional and evaluative significance of subsidized membership within a social system, instrumentalizes actions aimed at health promotion. The evidence recovered in this study indicates the need for collective actions to promote or maintain the social support for members of the trans community (21,(25)(26)(27) ; the role of the media (28) ; the support of friends, family, and other contacts of significance to the person (27) ; and greater family involvement in the transition process (27) , since these are factors that precede the formation of a social identity for the transgender person.…”
Section: Defining Characteristicsmentioning
confidence: 78%
“…The concept of social identity of the transgender person highlights the existence of two groups: the internal, in which one is inserted, also known as "us", a group that transmits an idea of proximity; whereas the external group would be the one in which they are not inserted, i.e., "them", a distant relationship (21) . Thus, it is possible to affirm that the desire to be part of the group that differs from the biological designation leads to the perception of a lack of both belonging and social recognition, characterizing this group, initially, as "external".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other studies (Dixon et al, 2007; Dovidio et al, 2010) have demonstrated that contact with an outgroup member was associated with less support for policies aimed at reducing group inequality. Although the generation of more positive intergroup attitudes is beneficial, promoting outcomes more closely tied to equalizing conditions between groups—such as policy support—is critical (see MacInnis & Hodson, 2019), especially examining policies that serve to damage or disempower disadvantaged groups, when the major focus thus far has been on examining support for policies aimed at restoring group equality (see Hässler et al, 2020; Reimer et al, 2020). As such, using a context-sensitive approach, the current research is focused on examining associations between intergroup contact and support for policies damaging to immigrants and refugees residing in Canada.…”
Section: Intergroup Contact Attitudes and Policy Supportmentioning
confidence: 99%
“…The best strategy is the facilitation of social movement and encouraging the critical alterity from the gendered group such as women and LGBT enhancing everyday dialogue which has potential to counter the prejudice in Dr. Chetan Sinha, OP Jindal Global University, Sonipat Email: sinchetan@gmail.com better way. Thus, the positive intergroup contact fosters the sense of inclusiveness and construction of new social identities (Reimer, Kamble, Schmid, & Hewstone, 2020).…”
Section: Conclusion: Brain Gender and Social Changementioning
confidence: 99%